Respuestas

2013-03-29T23:17:44+01:00

1) -7x^2 + 35 = 0

 -7x^2 = -35  / *-1

7x^2 = 35

x^2 = 35/7

x^2 =  5

x = +V5 y -V5 <- Soluciones

 

2) 3x^2 - 70=0

3x^2 = 70

x^2 = 70/3

x = +V70/3 y -V70/3

 

3)3x^2 - 27 = 0

3x^2 = 27

x^2 = 27/3

x = 9 y -9

 

4)4x^2 + 20 = 0

4x^2 = -20 

x^2 = -5

x = V-5 ó -V-5   (V5i ó -V5i)

 

5) -2x^2 +256 = 2x^2

 

-4x^2 = -256

x^2 = 64

x = 8 ó -8

 

6) (x-12)(x+12) = 0

x1 =  

(x -12 ) = 0 / (x+12)

(x-12) = 0

x1 = 12

x2 =

(x+12) = 0/(x-12)

x+12 = 0

x2 = -12

Soluciones = {12 , -12}

 

7.-

lo mismo que lo anterior

(x+5)(x-5)=0

x1 = -5

x2 = 5

 

8) 1,6x^2 = 0,144

x^2 = 0,144 : 1,6

x^2 = 0,09

x = V0,09

x = 0,3 ó -0,3

 

9.)   -x^2 + 16 = 0

-x^2 = -16 /*-1

x^2 = 16 / Raíz (V)

x = 4  y -4

 

El 4° debe estar mal copiado no creo que ya te pasen el número i.

 

Saludos.

2013-03-29T23:38:27+01:00

1) -7x^2 + 35 = 0

 -7x^2 = -35  / *-1

7x^2 = 35

x^2 = 35/7

x^2 =  5

x = +V5 y -V5 <- Soluciones

 

2) 3x^2 - 70=0

3x^2 = 70

x^2 = 70/3

x = +V70/3 y -V70/3

 

3)3x^2 - 27 = 0

3x^2 = 27

x^2 = 27/3

x = 9 y -9

 

4)4x^2 + 20 = 0

4x^2 = -20 

x^2 = -5

x = V-5 ó -V-5   (V5i ó -V5i)

 

5) -2x^2 +256 = 2x^2

 

-4x^2 = -256

x^2 = 64

x = 8 ó -8

 

6) (x-12)(x+12) = 0

x1 =  

(x -12 ) = 0 / (x+12)

(x-12) = 0

x1 = 12

x2 =

(x+12) = 0/(x-12)

x+12 = 0

x2 = -12

Soluciones = {12 , -12}

 

7.-

lo mismo que lo anterior

(x+5)(x-5)=0

x1 = -5

x2 = 5

 

8) 1,6x^2 = 0,144

x^2 = 0,144 : 1,6

x^2 = 0,09

x = V0,09

x = 0,3 ó -0,3

 

9.)   -x^2 + 16 = 0

-x^2 = -16 /*-1

x^2 = 16 / Raíz (V)

x = 4  y -4